EVALUATION OF HUMAN INFLUENCE ON THE PROCESS OF FORMATION OF GEOMORPHIC AND ECOLOGICAL SITUATIONS OF THE SHIRAK REGION (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
In the work the qualitative and quantitative evaluation of the factor of human influence on the geomorphic and ecological situation is introduced. Two types of anthropogenetic morphogeny have been introduced and indicated. Scale, depth and intensity of human influence on the relief and its elements have been evaluated and classified. Some laws and characteristics of human factors in the development of the relief of Shirak Region have been revealed. The chart map of Shirak Region of anthropogenetic relief changes and of natural consistence have been formed according to hypsometric zones.
Keywords: Shirak Region; anthropogenetic morphogeny; human factors; hypsometric zones